DETERMINANTS OF PROFITABILITY: A STUDY ON CERAMIC INDUSTRY IN BANGLADESH - Sharma, Iehit (Journal of Business And Entrepreneurship, 2022)
This study aimed to establish the key determinants of the profitability of ceramic companies. For this purpose the data of all ceramic companies were selected from DSE. The research period covered from 2015-16 to 2020-21. Return on Assets (ROA) and Return on Equity (ROE) were used as the indicators of profitability, while Management efficiency, Capital intensity, Firm size, Sales growth, Liquidity, Working capital, Leverage, Annual inflation and GDP annual growth were used as the independent variables. Pearson's correlation and ordinary least squares regression models were used to establish the relationship between profitability and its different determinants. The regression analysis results showed that liquidity and firm size have a statistically significant positive impact on profitability along with sales growth, capital intensity, management efficiency. On the other hand, working capital had a negative impact on profitability; others had no significant impact on profitability. Therefore, this research concludes that we should give more emphasize on liquidity and firm size for increasing ceramic companies' profitability.